UPAYA MENINGKATKAN MINAT BELAJAR DENGAN MEMAKSIMALKAN PENGGUNAAN ALAT PERAGA - Suyatni, Suyatni (JURNAL PENA EDUKASI, 2018)
Abstract: Classroom action research generally aims to improve the quality of learning for first grade students of SD Negeri 017141 Perk. Gunung Melayu district Rahuning. specifically aimed at: 1. Efforts to Increase Interest in Learning by Maximizing the Use of Teaching Aids on Mathematics Lessons on Theme Material Experiences of Class I Students of SDN 017141 Perk. Gunung Melayu district Rahuning academic year 2016/2017; 2. Describe the management of Mathematics learning. This classroom action research is carried out in 2 cycles, each cycle consisting of planning, implementing actions, observing and reflecting. Classroom action research was conducted in class I SD Negeri 017141 Perk. Gunung Melayu district Rahuning which amounted to 20 students. The subjects of this study were first grade Mathematics teachers and first grade students of SD Negeri 017141 Perk. Gunung Melayu district Rahuning, data is collected through observation, interviews, tests, and documentation studies. Keywords: Interest in Learning, Teaching Aids Abstrak: Penelitian tindakan kelas secara umum bertujuan untuk meningkatkan kualitas pembelajaran untuk peserta didik kelas I SDN 017141 Perk. Gunung Melayu Kec. Rahuning. secara khusus bertujuan untuk : 1. Upaya Meningkatkan Minat Belajar Dengan Memaksimalkan Penggunaan Alat Peraga Pada Pelajaran Matematika Materi Tema Pengalaman Siswa Kelas I SDN 017141 Perk. Gunung Melayu Kec. Rahuning TP. 2016/2017; 2. Mendeskripsikan pengelolaan pembelajaran Matematika. Penelitian tindakan kelas ini dilaksanakan dalam 2 siklus, setiap siklus terdiri dari perencanaan, pelaksanaan tindakan, pengamatan dan refleksi. Penelitian tindakan kelas dilaksanakan dikelas I SDN 017141 Perk. Gunung Melayu Kec. Rahuning yang berjumlah 20 orang siswa. Subjek penelitian ini adalah guru Matematika kelas I dan siswa kelas I SDN 017141 Perk. Gunung Melayu Kec. Rahuning, data dikumpulkan melalui observasi, wawancara, test, dan study dokumentasi. Kata kunci: Minat Belajar, Alat Peraga